BEAM MODELING FOR PGNAA EXPERIMENTAL FACILITY AT KARTINI REACTOR - Tegas Sutondo (Website, 2015)
BEAM MODELING FOR PGNAA EXPERIMENTAL FACILITY AT KARTINI REACTOR. A feasibility study on possible use of Kartini reactor’s beam port for Prompt Gamma Neutron Activation Analysis (PGNAA) experimental facility is going on. This work is part of the revitalization program activities of Kartini research reactor, including utilization of the available irradiation facilities. This paper presents results of beam modeling at the tangential beam port to get neutron beam meeting the specified criteria. The study was conducted by means of simulations using MCNPX code. The result concludes that there are several possible variations of collimator models that can provide neutron beam meeting the specified criteria and that tangential beam port is considered to be feasible enough for the purpose of PGNAA experimental facility